1995
DOI: 10.1159/000134107
|View full text |Cite
|
Sign up to set email alerts
|

Transcription patterns of sequences on human chromosome 21

Abstract: The polymerase chain reaction (PCR) was used to screen embryonic, fetal and adult human cDNA libraries for transcription on chromosome 21q22.1→q22.3. Seventy-three pairs of oligonucleotide primers on chromosome 21, used previously to screen a fetal brain cDNA library, were applied to analyze 41 different cDNA libraries. Only phage eluate (and therefore no DNA isolation) was required for this sensitive screening. Sixty primer pairs were positive with at least one cDNA library, indicating that the majority of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Contamination by genomic DNA resulting in the amplification of introns was not detected by the gel-PCR ethidium bromide, SYBR green, or Southern blotting methods, further demonstrating that genomic DNA contamination is not a significant problem. In addition, albeit impractical for large-scale screening, the Southern blotting method confirmed the accuracy of positive results obtained by the fluorescent-PCR and the original gel-based PCR method (Buraczynska et al 1995;Chiang et al 1995;Kurnit et al 1995); no false positives were observed and the only potential false negatives involved rarer messages. For abundant messages [denoted as (3) in the last column of Table 4], there is essentially complete concordance, with all four methodologies being positive.…”
Section: Semiquantitative Analysis: Transcriptional Abundancesupporting
confidence: 53%
See 1 more Smart Citation
“…Contamination by genomic DNA resulting in the amplification of introns was not detected by the gel-PCR ethidium bromide, SYBR green, or Southern blotting methods, further demonstrating that genomic DNA contamination is not a significant problem. In addition, albeit impractical for large-scale screening, the Southern blotting method confirmed the accuracy of positive results obtained by the fluorescent-PCR and the original gel-based PCR method (Buraczynska et al 1995;Chiang et al 1995;Kurnit et al 1995); no false positives were observed and the only potential false negatives involved rarer messages. For abundant messages [denoted as (3) in the last column of Table 4], there is essentially complete concordance, with all four methodologies being positive.…”
Section: Semiquantitative Analysis: Transcriptional Abundancesupporting
confidence: 53%
“…In all five cases, we observed the most abundant transcription in the expected tissues. Table 4 compares the sensitivity of four methods: the gel-PCR assay m o n i t o r e d by ethidium bromide (Buraczynska et al 1995;Chiang et al 1995;Kurnit et al 1995) or SYBR green (Schneeburger et al 1995) staining, the gel-PCR assay monitored by Southern blotting with the gene in question as a radiolabeled probe, and the fluorescent-PCR assay. For the most abundant expression (defined as positivity in the fluorescent-PCR assay at the minimum number of cycles, including all tissues where transcription was known previously to occur), there was positivity with all four techniques for all 34 tissues.…”
Section: Fluorescent-pcr Reactionmentioning
confidence: 99%
“…Further, on the basis of the high level of methylation in this cytogenetic band, some authors (Yu et al, 1997) have hypothesized that, though poor in housekeeping genes, this region may not be devoid of coding sequences, but may rather contain representatives of large gene families. Currently, the development of expression maps is contributing to the isolation of new genes, especially in intractable regions such as 21q11-q21 (Kao et al, 1994;Kurnit et al, 1995;Yaspo et al, 1995;Delabar et al, 1998).…”
Section: Introductionmentioning
confidence: 99%